Improving delivery of shared public services in Kampala capital city authority Uganda / Nabukeera Madinah - Madinah, Nabukeera (2014)
The increasing importance to improve efficiency in Public sector in Uganda allowed the innovative shared service model to operate with a view of lowering costs, improving efficiency and service delivery. This thesis aims to explore whether application of the model resulted into service satisfaction and service quality in Kampala Capital City Authority (KCCA). The theoretical propositions underlying shared services are the transformation of service delivery which leads to improvement and the current researcher has sought the answer to this question by examining the cost, quality and social welfare (CQS) dimensions in KCCA, Uganda. In addition the social welfare, cost, economies of scale, efficiency, effectiveness equity, quality and quantity (SCEEEEQQ) has also been examined as a measurement instrument. A cross sectional study used a questionnaire as an instrument involving 573 employees, former employees and residents of KCCA as respondents. In addition interviews were carried out as another source of data to support in discovering the in-depth model of sharing. Cluster sampling was used were clusters are parishes and strata are the divisions. The data has been analyzed using a Statistical Package for Social Science (SPSS Version 16) and NVIVO where analysis for reliability i.e., factor analysis, correlation, regressions and hierarchical regression have been performed. Results further indicate that, sharing solid waste management has improved service delivery, reduced costs, improved efficiency and effectiveness, service satisfaction, social welfare and service quality though far from optimal level and there was no documented evidence to show that costs and economies of scale reduced although quantitative data supports. Further, qualitative findings indicate that the model was initiated two years iv ago, all the five divisions of KCCA are involved in the sharing, a mixed model i.e., formal and informal is being applied, they share transport, heavy equipments, landfill and human resources, the major reasons for sharing are economic driven i.e., lack of resources. This study offers recommendations for theory, research and policy. Overall KCCA is effective and efficient in delivering solid waste services using a sharing model and the model’s success was also dependent on the informal approach of its implementation process and a clear understanding of the risks and benefits. This research bridged the gap in the literature through empirical evidence and novel insights on the impact of shared services on service quality and service satisfaction in public-public sector in Ugandan context. The findings of this research may enable policy makers to consider shared services as a preferred model of service delivery.